ISOLATION AND MOLECULAR CHARACTERIZATION OF A GENE CODING FOR DEFENSIN FROM AN EGYPTIAN MAIZE HYBRID (SC 168) - N. A. T. Al Kashgry; H. H. Abulreesh; 3; I. A. El-Sheikh; Y. A. Almaroai; R. Salem; G. E. H. Osman (Journal of Animal and Plant Sciences, 2020)
Plant genome analysis has disclosed that genes encoding defensins are highly abundant in most plant genomes. Maize presents a good source for novel antifungal peptide-encoding genes. In this study, we isolated a defensin gene (MzDef) from Egyptian maize (Zea mays L.) hybrid yellow single cross 168 for the first time with a size similar to the isolated plant defensin-encoding genes. A fragment of approximately 245 bp in length was amplified by PCR. The sequence analysis revealed the presence of a single 108 bp open reading frame (ORF), which encodes a signal peptide of 35 amino acids. Furthermore, this sequence showed homology with the super-family of plant defensins in general and to the maize in particular. Noticeably, the matching sequences mainly belonged to monocots. Phylogenetic tree showed the relation with other defensin-encoding genes isolated from different plants. The sequence showed high homology with amylase inhibitor-like protein and low molecular weight cysteine-rich protein. The ratios of identity and divergence between the compared ORFs were determined. In order to predict the properties of defensin, its ORF was translated into amino acids. Our analysis confirms that the isolated gene belongs to the family of plant defensins, further investigation is required to explore its antifungal activities.
Keywords: Defensin; Maize; Amylase inhibitor; cysteine-rich protein; PCR